”Jag tar varken kristendom eller islam på allvar, jag går efter vad jag själv tycker” - Westerberg, Boel (Educare, 2007)
This article is based on a Research-project called Upper Secondary-pupils´ Creation of Meaning in the Multicultural Classroom. In this project I and my fellow researcher followed a class during their three years in Upper Secondary School, observing them in lessons and performing interviews with them twice a term. In this article, my main interlocutor/informant, who goes by the name Argita in the text, is a girl of Albanian background, but who has had almost all her education in Swedish schools. I focus on three problems, or questions: how and when are existential questions discussed in the classroom and which role do they play in the teachers’ choice of subjects? Second, I am interested in the multicultural classroom, or the culturally heterogeneous classroom, as I prefer to call it. What does it denote and add up to? I suggest that “multicultural” implies much more than just immigrants and Swedes meeting in class. It is also about boys and girls, pupils with different economic and cultural background and pupils representing different youth-cultures. Finally, I discuss what is meant by the terms “offering meaning” and “creating meaning” in school. Does all teaching offer meaning to pupils? I do not think so. Rather, I think that pupils, such as Argita, have a capacity to create meaning, in their schoolwork and in their lives, regardless of what school has to offer.